MENIMBANG POLIGAMI DALAM HUKUM PERKAWINAN - Ali Imron (Qistie Jurnal Ilmu Hukum, 2012)
Marriage is essentially a reunification of men and women consisting of elements of  soul and body are  fused  into one  in a household  frame  for  emotional and physical welfare. Regulation of marriage embraced the principle that a man may only have a wife and vice versa. The court may grant permission  to  the husband  to a wife more than a certain requirements. Qualitative and quantitative Justice as a condition of polygamy difficult and even impossible to be realized. Polygamy is synonymous with  the exploitation of women  for  the  sake of greed and  sexual  lust. Key words: Marriage, Polygamy,  Islamic Law